(untitled) (Journal of Humanitarian and Applied Sciences, 2023)
Abstract: Abstract This research deals with two manifestations of the phenomenon of rhetorical intensification. Namely: briefness of brevity, and metaphor in the hadith of the Messenger of Allah. They are among the most important Arabic rhetoric arts, the most effective on the soul , the most exaggerated meanings, because of their strong relevance to persuasion, pleasure ,and addressing intellectual and feeling. The Messenger’s speech , which are the origin of the statement, and the essence of the rhetoric, have hardly been devoid of them. The research needed to go through the applied and analytical approaches to study evidence from Al- Hadith Al-Sharif (noble hadith), according to the plan presented in the introduction to the research..